Strategic Communication for Post-Consumption Engagement in Sustainable Fashion: Extending Consumer Responsibility - Iliashenko, Iuliia; Pezzetti, Roberta; Gazzola, Patrizia (European Journal of Sustainable Development, 2025)
The fashion and textile industry is increasingly confronted with critical sustainability challenges, particularly concerning the post-consumer textile waste generation provoked by the rapid change of consumption trends. While progress has been demonstrated in the domain of sustainable production approaches development, the post-consumption phase as an essential dimension within the circular economy paradigm remains insufficiently addressed within both academic discourse and industrial strategy. This paper introduces the conceptual framework for the Extended Consumer Responsibility (ECR) as a complementary to Extended Producer Responsibility strategic approach to foster sustainable consumers behaviour, providing reconsideration of the post-consumption as a strategic frontier for sustainable value creation by engaging consumers actively after the use phase. Based on the systematic literature review and EU policy-driven key post-consumption strategic elements for circular fashion and textile related to the consumers awareness and engagement within the REsolve frame: reuse, repair recycling, this study discloses the potential to enhance sustainability through digitalized post-purchase communication strategy development that leveraging advanced digital technologies encourages closed-loop behaviours and long-term value co-creation in the evolving fashion ecosystem. Moreover, it highlights the strategic role of digital transformation processes as enablers of dynamic and personalized communication, supporting the development of transparent, purpose-driven post-consumption engagement frameworks. Keywords: Sustainable consumption, fashion industry, consumers behaviour, post-consumption, communication strategy, digital technologies